Geothermal exploration methods and results: inland states - Maxwell, J. C. (Los Alamos Scientific Laboratory, 1979)
The Los Alamos Scientific Laboratory (LASL) geothermal exploration sequence includes: (a) review of AAPG/USGS gradient maps, (b) literature search, (c) consideration of potential markets, (d) groundwater silica geothermometry, (e) analysis of bottom-hole temperatures, (f) heat flow measurement of available wells, and (g) drilling of new test holes. This procedure has located anomalies near Syracuse, NY (36/sup 0/C/km, 56/sup 0/C silica max.), near Buffalo, NY (36/sup 0/C/km, 65/sup 0/C silica max.), southeast Ohio, western and southwestern Nebraska, and three new warm springs in Arkansas. Other investigations have found high heat generation (14 to 25 HGU) in the White Mountain batholith NH (170/sup 0/C calculated at 6 km depth), uparching of the Adirondac Dome, NY, and potentially economic electricity from hot brines in southwest Arkansas.